Acetylation of fructose-bisphosphate aldolase-mediated glycolysis is essential for Bombyx mori nucleopolyhedrovirus infection. (September 2022) - Gao, Xu; Xu, Siqi; Mo, Yuqian; Zhu, Yajie; Chen, Xi; Miao, Meng; Quan, Yanping; Yu, Wei
Abstract: Bombyx mori nucleopolyhedrovirus (BmNPV) is a baculovirus that infects silkworms, and its interaction with silkworm has been considered an important model in the field of insect virology. Accumulating evidence indicates that most viruses promote glycolytic metabolism in host cells to favor infection. However, similar reports are lacking in insects, especially in the area of post-translational modifications of proteins. In this study, we found that BmNPV infection induced the acetylation of fructose-bisphosphate aldolase (ALDO) on lysine 42 (K42) to promote its enzyme activity. To explore the underlying mechanisms, site-directed mutagenesis of deacetylated mimic (K/R) was performed. The results demonstrated that K42 acetylation promoted viral proliferation by exacerbating the glycolytic flux induced by BmNPV infection, which resulted in increased ATP, glucose uptake and lactate accumulation. Inhibiting glycolysis with 2-deoxygucose (2DG) revealed that glycolysis was essential for optimal BmNPV infection. Finally, we showed that BmNPV-infected cells enhanced the transcription of glycolysis-related genes, including Glut1, Hk2 and Ldh . In parallel, K42 acetylation of ALDO also promoted the expression of these genes. Therefore, acetylation of ALDO could be considered a regulator of BmNPV-induced glycolysis. These finding provide insights into the interaction between silkworm and BmNPV. Graphical abstract: Image 1 Highlights: BmNPV invasion induces up-regulation of acetylation level at ALDO K42 residue. Glycolysis is required for efficient BmNPV multiplication. K42 acetylation of ALDO promotes viral proliferation by exacerbating the glycolytic flux induced by BmNPV infection. K42 acetylation of ALDO up-regulates glycolysis-related genes.